Analysis of Demodulation Methods of Tilted Fibre Bragg Gratings Based on the Local Shift of the Cladding Mode Group - Sławomir Cięszczyk; Krzysztof Skorupski; Patryk Panas (Applied Sciences, 2024)
Tilted fibre Bragg gratings are optical fibre structures used as sensors of various physical quantities. However, their most popular application is to measure the refractive index of liquids. In such applications, it is important to obtain high measurement accuracy and the ability to distinguish two slightly different values of the refractive index. For this purpose, not only an appropriate periodic structure is needed, but also a demodulation method. We propose averaging the shift of a group of cladding modes. We use the TFBG grating, of which not all cladding modes exceed the cut-off limit. Such modes are not subject to leakage but only to shifts under the influence of SRI changes. To determine the average shift of a group of modes, we analyse cross-correlation algorithms of intensity-transformed optical spectra. Next, the cross-correlation main lobe is analysed by the centroid method, the Fourier phase and the Hilbert transform. Furthermore, phase changes of the main Fourier frequency are used to estimate a shift of part of the optical spectrum. Additionally, we propose the correction of the determined shift using a shift of another group of modes of the same TFBG grating.